PCR based assay for the detection of Alternaria brassicicola in Crucifers - and P. CHOWDAPPA, PRATIBHA SHARMA*, SWATI DEEP, MANIKA SHARMA, DINESH SINGH BHATI (Indian Phytopathology, 2013)
Alternaria brassicicola (Schwein) Wiltshire and A. brassicae (Berk) Sacc. are important necrotrophic fungal pathogens causing black leaf spot disease on crucifers including vegetable and oilseed crops. In India, the mixed infection caused by both the species is a common phenomenon occurring in the field where the symptom becomes confusing and both the species become indistinguishable. The disease being seed borne requires an easy, fast and reliable detection method. A simple conventional polymerase chain reaction based assay was developed for the detection and identification of A. brassicicola using specific primers designed from nuclear ribosomal internal transcribed spacer (ITS) regions. A specific fragment of 600bp was amplified by PCR using primers Acola-sens: 5′-GCA GCA TCT GCT GTT GGG G-3′ and Acola-reverse: 5′-CAA GGT CAG CAT CCA TAA AGC C-3′ for A. brassicicicola isolates, with a detection limit of 100pg. The primers did not support amplification when tested on A. brassicae, A. alternata, and A. porri. The primers could also detect seed-borne infection of A. brassicicola.